Determining sources of reactive mercury compounds in Reno, Nevada, United States - Gustin, Mae Sexauer; Dunham-Cheatham, Sarrah M.; Choma, Nicole; Shoemaker, Kevin T.; Allen, Natalie (Frontiers in Environmental Chemistry, 2023)
There is much uncertainty regarding the sources of reactive mercury (RM) compounds and atmospheric chemistry driving their formation. This work focused on assessing the chemistry and potential sources of RM measured in Reno, Nevada, USA, using one year of data collected using RM Active Systems. In addition, ancillary meteorology and criteria air pollutant data, HYSPLIT analyses, and a generalized linear model (GLM) were applied to better understand RM observations. During the year of sampling, a fire event impacted the sampling site, and GEM and PBM concentrations increased, as did HgII-S compounds. Data collected on a peak above Reno showed that RM concentrations were higher at higher elevation, and compounds found in Reno were the same as those measured on the peak. HYSPLIT results demonstrated RM compounds were generated inside and outside of the basin housing Reno. Compounds were sourced from San Francisco, Sacramento, and Reno in the fall and winter, and from long-range transport and the marine boundary layer during the spring and summer. The GLM produced correlations that could be explained; however, when applying the model to similar data collected at two other locations, the Reno model did not predict the observations, suggesting that sampling location chemistry and concentration cannot be generalized.